2022
DOI: 10.48550/arxiv.2201.08545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of a cool, metal-rich gas reservoir in the outskirts of z ~ 0.5 clusters

Sapna Mishra,
Sowgat Muzahid

Abstract: We built the first-ever statistically significant sample of ≈ 80, 000 background quasar -foreground cluster pairs to study the cool, metal-rich gas in the outskirts (> R 500 ) of z ≈ 0.5 clusters with a median mass of ≈ 10 14.2 M . The sample was obtained by cross-matching the SDSS cluster catalog of Wen & Han (2015) and SDSS quasar catalog of Lyke et al. (2020). The median impact parameter (ρ cl ) of the clusters from the quasar sightlines is 2.4 Mpc (median ρ cl /R 500 = 3.6). A strong Mg ii, along with marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recently, Artale et al (2022) found that Mg II, C II, and Si IV are efficient tracers of the halo gas in dense environment, whereas Ne VIII, N V, O VI, and C IV are better tracers of warm hot and low-density gas (WHIM) inside filamentary structure at large scales (and z=0). In particular, the small fraction of halo gas phase inside clusters (with T < 10 5 K and n H > 10 −4 cm −3 ) is supposed to be condensed gas inside halos in high-density and low-temperature star-forming regions, as recently observed via Mg II absorption lines by Lee et al (2021), Anand et al (2022), andMishra &Muzahid (2022). For example, Lee et al (2021) showed that Mg II absorbers are more abundant inside clusters than outside them (> 2R 200 ).…”
Section: The Gas Phasesmentioning
confidence: 81%
“…Recently, Artale et al (2022) found that Mg II, C II, and Si IV are efficient tracers of the halo gas in dense environment, whereas Ne VIII, N V, O VI, and C IV are better tracers of warm hot and low-density gas (WHIM) inside filamentary structure at large scales (and z=0). In particular, the small fraction of halo gas phase inside clusters (with T < 10 5 K and n H > 10 −4 cm −3 ) is supposed to be condensed gas inside halos in high-density and low-temperature star-forming regions, as recently observed via Mg II absorption lines by Lee et al (2021), Anand et al (2022), andMishra &Muzahid (2022). For example, Lee et al (2021) showed that Mg II absorbers are more abundant inside clusters than outside them (> 2R 200 ).…”
Section: The Gas Phasesmentioning
confidence: 81%